A diversity profile of total bacteria (culturable and unculturable) as aquaculture marine water source of in central marine bio industry (BBIL) Mataram, Indonesia. Issue 1 (1st June 2022) - Hastuti, Yuni Puji; Fatma, Yuli Siti; Nirmala, Kukuh; Supriyono, Eddy; Dwiono, Sigit A.P.; Munandar, Aris; Hamzah, Aris Sando; Tridesianti, Siska; Sudarmo, Agnes Puspitasari
Abstract: The bacterial community plays a pivotal role in the quality of water sources for aquaculture activities, affecting the survival of cultured animals. In the present study, bacteria inhabiting seawater in Mataram were analyzed using culturable and unculturable analysis. Total bacteria cultured in SWC (seawater complete) medium had an abundance of 4.5 × 10 7 CFU mL -1 . Nitrifying, denitrifying, and DNRA (dissimilative nitrate reduction to ammonium) bacteria were found in an abundance of 1.15 × 10 7 CFU mL -1, 7.7 × 10 6 CFU mL -1, and 5.6 × 10 6 CFU mL -1, respectively. Analysis of total bacteria performed by the Illumina MiSeq platform using the V3–V4 hypervariable regions of 16S rRNA gene indicated that the majority of the bacterial sequences related to Proteobacteria (84.2%), followed by Firmicutes (10.2%), Acidobacteria (1.5%), Bacteroidetes (1.4%), and Chloroflexi (1%). Family Piscirickettsiaceae, belonging to the order Thriotrichales, was observed as the most prevalent group accounting for 20.9%. In this study, Proteobacteria, the most common phylum, was dominated by Gammaproteobacteria. At the genus level, Alteromonas, Marinobacterium, and Methylophaga appeared as the top three prevalent groups inhabiting seawater in Mataram. Meanwhile, the top five bacterial species in seawater were Alteromonas bacterium, Methylophaga sp., Nautella italic, Ruegeria mobilis, and Pseudoalteromonas phenolica .